Bagthorpes abroad - Cresswell, Helen (New York : Macmillan, 1984)
Chronicles the further adventures of the eccentric Bagthorpe family as they go on vacation to a reputedly haunted house in Wales.
Bulletin (Center for Children's books).
School Library Journal.
Wilson's Junior High School.
6.7
6.7
5-8.
Keywords: Children's stories, English; Family life -- Fiction; Vacations -- Fiction; Family life -- Fiction; Vacations -- Fiction; Wales -- Fiction; Wales -- Fiction